ANALISIS PENGARUH LINGKUNGAN KERJA FISIK TERHADAP KELELAHAN KERJA KARYAWAN BAGIAN MOULDING DI PT ABC - ronanda tambunan, edward; Zetli, Sri (Computer Science and Industrial Engineering, 2023)
The purpose of this study was to determine the physical work environment conditions felt by employees in the moulding section, determine the level of burnout of employees in the molding section and determine the relationship between the physical work environment and the fatigue of employees in the molding section. This research was conducted at the molding department at PT ABC. The population in this study amounted to 50 employees of the molding department at PT ABC. The results showed that: 1) Based on the results of measurements of the room temperature variable, the average value was 20.14 with a percentage value of 72%, it can be concluded that molding employees at PT ABC experience excessive heat while working. This category is not good enough that it causes work fatigue to occur, 2) Based on the measurement results of the work fatigue variable, 37 respondents experienced moderate fatigue and 6 respondents experienced mild fatigue with an average of 77.6 with a percentage of 65%. It can be concluded that molding employees at PT ABC experience fatigue with middle and upper levels at work. This is caused by the unfavorable room temperature which causes work fatigue in employees, and 3) Based on the results of the influence test measurements, it shows that room temperature has a significant effect on the work fatigue of molding employees at PT ABC.